2012
DOI: 10.5296/bms.v3i1.1851
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Diversity in the Board and Corporate Tax Planning in American Firms

Abstract: This study examines the effect of demographic gender diversity on corporate tax planning. Using a sample of 300 firms (S&P 500) for the 1996-2009 periods, results indicate that gender diversity on the board is not significant and doesn't have an effect on tax planning. Board independence enhances tax practice. ROA is significant and associated with tax planning. Board size and firm size do not exhibit significant relations. We contribute to the literature of gender by proposing a new tax framework. We propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…The number of female leaders is relatively small (7.7%) so that the behavior of female executives cannot influence the results of decisions taken, especially in tax avoidance measures. The research results are supported by previous research that has been carried out, that is research conducted by Khaoula and Mohamed [17] which explains that diversity in terms of opinions, knowledge, and experiences due to gender diversity in the company's board of directors, are less able to create tax-planning strategies, which is appropriate to minimize the company's tax burden.…”
Section: Gender Diversification Effect On Tax Avoidancesupporting
confidence: 77%
“…The number of female leaders is relatively small (7.7%) so that the behavior of female executives cannot influence the results of decisions taken, especially in tax avoidance measures. The research results are supported by previous research that has been carried out, that is research conducted by Khaoula and Mohamed [17] which explains that diversity in terms of opinions, knowledge, and experiences due to gender diversity in the company's board of directors, are less able to create tax-planning strategies, which is appropriate to minimize the company's tax burden.…”
Section: Gender Diversification Effect On Tax Avoidancesupporting
confidence: 77%
“…They attribute more ethical values to female than to male directors, which indicates that men have a better attitude to influence the decision-making process of adopting a tax strategy. In contrast, Khaoula et al [60] do not show any significant relationship between gender diversity in a corporate board and the decision-making process in adopting a tax strategy.…”
Section: The Moderating Role Of the Board Of Directors' Gender On Thementioning
confidence: 80%
“…Lanis [21] reported that the board of directors numbers has a significant influence on the tax aggressiveness formulation. In contrast, Khaoula [22] argues that there is no relationship between board standard and tax aggressiveness in the American context. They find that the number of directors do not affect the strategy to minimize the tax expense.…”
Section: Tax Aggressivenessmentioning
confidence: 97%